Coumarins and lignans from the roots of Zanthoxylum nitidum. (April 2022) - Su, Jian-Hui; Wang, Ming-Qiang; Zhu, Li-Ping; Yang, Wei-Qun; Jiang, Shi-Qin; Zhao, Zhong-Xiang; Sun, Zhang-Hua
Abstract: The phytochemical investigation of the Chinese medicine Zanthoxylum nitidum led to the isolation of a new coumarin glycoside (1 ), seven known coumarins (2 –8 ) and two known lignan glycosides (9 –10 ). Their structures were elucidated based on extensive spectroscopic methods (HRESIMS, 1D and 2D NMR experiments) and by comparison with literature data. The new compound (1 ) was a linear furanocoumarin glycoside. Among these known compounds, Compound 10 was isolated from Z. nitidum for the first time, while compounds 2, 4, 5, and 9 were firstly recovered from the Rutaceae family. The lignan glycosides (9 –10 ), which possessed a 4-hydroxy-3, 5-dimethoxycinnamic ester at the glycoside portion, were rare in plants. The chemotaxonomic significance of these isolated compounds has also been discussed. Graphical abstract: Image 1 Highlights: A new coumarin glycoside (1 ), seven known coumarins (2 –8 ) and two known lignan glycosides (9 –10 ) were isolated from Zanthoxylum nitidum. Zanthoxylumoside A (1 ) was a linear furanocoumarin glycoside. Compounds 9 –10, which possessed a 4-hydroxy-3, 5-dimethoxycinnamic ester at the glycoside portion, were rare in plants.